Can creative podcasting promote deep learning? The use of podcasting for learning content in an undergraduate science unit. (8th January 2014) - Pegrum, Mark; Bartle, Emma; Longnecker, Nancy
Abstract This paper examines the effect of a podcasting task on the examination performance of several hundred first‐year chemistry undergraduate students. Educational researchers have established that a deep approach to learning that promotes active understanding of meaning can lead to better student outcomes, higher grades and superior retention of knowledge over time. We attempted to promote such an approach by setting a task that involved student collaboration, contextualisation of content, and communication through new media, specifically creative podcasting. Examination results were used as a source of empirical evidence of changes in understanding and retention that occurred for students who completed this task. In comparing results across 2 years on similar questions related to the podcasting topics, we found a statistically significant improvement after introduction of the podcasting task on the questions related to one of the topics on which students had actively created their own podcasts ("acids & bases"), but not on the other ("oxidisation and reduction"). Improved learning outcomes in the form of better understanding and retention over time in at least one case suggest that under some circumstances creative podcasting may indeed help to promote a deep learning approach.